2019
DOI: 10.1002/cae.22099
|View full text |Cite
|
Sign up to set email alerts
|

Development of an educational virtual reality training system for marine engineers

Abstract: In this study, an educational virtual reality training system named “DMS‐VLCC3D” has been developed to help students or marine engineers learn the working principle of the marine engineering system and improve their ability of practical operation in a more efficient and vivid way. During the stage of establishing the geometric model of the virtual marine engine room, optimization methods including instantiation modeling, functional nodes optimization, level of detail, and texture mapping optimization are adopt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 20 publications
(16 reference statements)
0
26
0
1
Order By: Relevance
“…This paper introduces the characteristics of testing, inspection and certification (TIC) industry. The theoretical background was discussed and suggested the laboratories to consider before they decided to implement the VR training system [13]- [15]. Some examples were discussed to explain pros and cons of VR training platform.…”
Section: Discussionmentioning
confidence: 99%
“…This paper introduces the characteristics of testing, inspection and certification (TIC) industry. The theoretical background was discussed and suggested the laboratories to consider before they decided to implement the VR training system [13]- [15]. Some examples were discussed to explain pros and cons of VR training platform.…”
Section: Discussionmentioning
confidence: 99%
“…Virtual Reality (VR) technology allows users to interact with different objects in a virtual environment [1]. Shen et al [2] found that virtual simulation, through VR technology, creates significant advantages including cost savings, time-savings, and improvements in training efficiency and safety in areas such as healthcare, construction, and manufacturing. Sherman and Craig [3] define VR technology as a medium composed of computer simulations that sense the user'sactionsandpositions and change or augment the feedback to the user's senses, creating the feeling of being present in the simulation, in other words, being mentally immersed.…”
Section: Introductionmentioning
confidence: 99%
“…The MVEM developed in this paper is very suitable for applications that require both fast running speed and in-cylinder pressure trace predictive capability, for example, this MVEM has been attempted to be used in a VLCC (Very Large Crude Carrier) marine engine room simulator [11].…”
Section: Introductionmentioning
confidence: 99%